Teknik Ikat dan Teks Filosofis: Analisis Etnografi Seni Ikat Rotan Totemik dalam Konstruksi Rumah Kun Suku Armati - Kelana Vhisnu Nugroho; Tindia Febriyati (Jurnal Multidisiplin Indonesia, 2026)
This study examines the ethnographic relationship between rattan binding techniques and philosophical meanings in the construction of the Kun House of the Armati Tribe in Sarmi, Papua. Vernacular architecture in this region reflects complex adaptations to environmental and cultural contexts, where the Kun House functions not as a residence but as a sacred ceremonial structure. The objective of this research is to analyze how rattan bindings operate simultaneously as structural technology and as a medium of material semiotics that encodes cosmological, social, and totemic meanings. The research employs an architectural anthropology approach with qualitative ethnographic methods, including interpretation of spatial structures, symbolic elements, and construction techniques. The findings reveal that rattan bindings possess dual functions: technically, they provide flexibility and resilience against environmental pressures; philosophically, they represent a symbolic system reflecting the three-world cosmology, social hierarchy, and ritual practices. Specific binding patterns such as Turatim, Maksurs, and Martemak encode meanings related to social solidarity, liminality, and natural cycles. The study concludes that rattan binding is not merely a construction method but a cultural text that integrates technical knowledge with symbolic meaning. Preservation efforts should therefore focus on safeguarding intangible knowledge systems alongside physical structures.